2020
DOI: 10.1039/d0py00728e
|View full text |Cite
|
Sign up to set email alerts
|

Covalently cross-linked polymer stabilized electrolytes with self-healing performance via boronic ester bonds

Abstract: Herein, the solid polymer electrolytes (SPEs) were designed and fabricated via the photopolymerization of the macromolecular crosslinker with boronic ester bonds and poly(ethylene glycol) diacrylate (PEGDA) with different molecular weights...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…In the SIPEs, anions are immobilized by covalently bonding with the polymeric backbones or by anion trapping agents so that the lithium ions associate with anions loosely by electrostatic interactions, resulting in a lithium-ion transference number of nearly close to 1. Despite abovementioned advantages of SIPEs, most of them suffer from cracks during the electrochemical process of LMBs. Therefore, the self-healing polymer electrolytes would be an effective strategy to heal cracks and restore its original property for LMBs. Polymer electrolytes with self-healing properties can be defined as dynamic covalent bond interactions and nondynamic covalent bond interactions. Jo et al designed and synthesized the self-healing SPEs with disulfide bond and hydrogen bond interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SIPEs, anions are immobilized by covalently bonding with the polymeric backbones or by anion trapping agents so that the lithium ions associate with anions loosely by electrostatic interactions, resulting in a lithium-ion transference number of nearly close to 1. Despite abovementioned advantages of SIPEs, most of them suffer from cracks during the electrochemical process of LMBs. Therefore, the self-healing polymer electrolytes would be an effective strategy to heal cracks and restore its original property for LMBs. Polymer electrolytes with self-healing properties can be defined as dynamic covalent bond interactions and nondynamic covalent bond interactions. Jo et al designed and synthesized the self-healing SPEs with disulfide bond and hydrogen bond interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The healed SPE displays no changes in the electrochemical performance of a battery. Li et al , reported boronic ester bonds and boroxine bonds in SPEs with healable properties. The boronic ester and boroxine-based SPEs presented excellent healable properties, high ionic conductivity, and good mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…olefin metathesis), 1,[33][34][35] acetals, 36 transesterifications (incl. boronates), [37][38][39][40][41][42][43] and reactions involving disulfides. 12,44 Among these, reactions that can generate carbon-carbon bonds are of special interest since transformations are responsible for building up the carbon backbone of organic molecules and materials.…”
Section: Introductionmentioning
confidence: 99%
“…To satisfy the increasing demand for energy storage devices such as portable electronic products and electric vehicles, the rechargeable lithium metal batteries (LMBs) have been widely applied in the field of energy storage due to their properties of light weight, high gravimetric energy densities, and long cycle life. The electrolyte is an important component of LMBs, which could play a crucial part in fast conduction of lithium ions and the electrochemical performance of LMBs. However, the commercial LMBs usually suffer from the potential safety issues such as flammability, leakage, and poor chemical stability because the liquid electrolytes consist of the organic carbonate solvents and lithium salt. To address the aforementioned problems, solid polymer electrolytes (SPEs) composed of a polymer host and disassociated lithium salt are used as effective alternatives for liquid electrolytes to alleviate the safety issues. Nevertheless, the relatively low ionic conductivity (<10 –6 S cm –1 ) of SPEs at room temperature prevents their extensive application in LMBs, especially for the most widely used poly­(ethylene oxide) (PEO)-based SPEs. The PEO-based SPEs usually have low ionic conductivity, which is ascribed to the semicrystalline region in the polymer matrix. Moreover, the poor contact interfaces between SPEs and solid electrodes could result in the deteriorated cycling performance. …”
Section: Introductionmentioning
confidence: 99%